MOTIVATION OF TEACHERS IN SENIOR HIGH SCHOOLS - Nur Faliza; Aditya; Rahmaniar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study examined the effect of communication, conflict, and leadership style on the teaching motivation of teachers in Banda Sakti subdistrict, Lhokseumawe City. This study used primary data obtained by distributing questionnaires to 173 respondents selected using the Proportional sampling technique. The data analysis method used was multiple linear regression with SPSS. The results showed that communication positively and significantly influenced the teaching motivation of teachers in Banda Sakti subdistrict, Lhokseumawe City, the conflict negatively and not significantly influenced the teaching motivation of teachers in Banda Sakti subdistrict, Lhokseumawe City, and transformational leaderships positive significantly influenced the teaching motivation of teachers in Banda Sakti subdistrict, Lhokseumawe City.